About the human rights on voluntary hunting in the context of the right to life - Vasilevich, Dmitry G. (Journal of the Belarusian State University. Law, 2019)
The article analyzes the contents of the human right to voluntary starvation in the context of the right to life. It shares the view expressed in the literature approach, according to which the right to life is not only a right to inviolability, but also the right to freedom to dispose of it. The refusal of the meal can be caused by various factors: the desire to get rid of the full body, improve the body, to raise children in line with their food culture, the desire in such a way (refusal of food) to terminate his life. Regarding these actions of people expressed various estimates and judgments. The law also has the relevant requirements, for example, to persons who are in prison for violation of which can be responsible. As practice shows, the cultivation among young people as a «standard» thin people often leads to serious health consequences. In some cases, the question of parental responsibility, if they pose a threat to their children. In other situations, a discussion takes place on the legality of forced power officials, refusing all food intake, which can lead to their death. We have maintained the position that the law should promote the preservation of life. In our Constitution, a person declared supreme goal and value of society and the state. With nutrition is closely related problem of doping in sport. The establishment in sports ban on the use of some existing drugs is under a certain moral and legal basis. However, not always the international organizations in the field of sports are taking the exact terms of the principles of legal solutions. The author expresses the position on the aspects mentioned above, appropriate proposals are made.
Keywords: the right to life; the right to free disposal of life; restrictions on the right to voluntary starvation